Пусть a>b>0 докажите что a³>b³, a³>ab², a⁴>a²b², a²b²>b⁴
a² - b² = (a - b)(a + b)
a³ - b³ = (a - b)(a² + ab + b²)
a>b>0 ⇒ a - b > 0 a > 0 b > 0
1. a³>b³
a³ - b³ > 0
(a - b)(a² + ab + b²) > 0 так как a - b > 0 по условию, вторая скобка > 0 как сумма положительных чисел чтд
2. a³>ab²
a³ - ab² > 0
a(a² - b²) > 0
a( a - b)(a + b) > 0 так как a и a - b > 0 по условию, вторая скобка > 0 как сумма положительных чисел чтд
3, a⁴>a²b²
a⁴ - a²b² > 0
a²(a² - b²) > 0
a²(a - b)(a + b) > 0 так как a и a - b > 0 по условию, вторая скобка > 0 как сумма положительных чисел чтд
4. a²b²>b⁴
a²b²- b⁴ > 0
b²(a² - b²) > 0
b²(a - b)(a + b) > 0 так как b и a - b > 0 по условию, вторая скобка > 0 как сумма положительных чисел чтд
а) 2(х-5)=9
2\x-10=9
2x=19
x=19/2
в)-(х+8)=3
-x-8=3
x=-8-3
x=-11
д) 7-3(х+1)=6
7-3x-3=6
7-3-6=3x
3x=-2
x=-2/3
ж) 2х-(7+х)=2
2x-7-x=2
x=2+7
x=9